Effects of Medium-Chain Fatty Acid Glycerides on Nutrient Metabolism and Energy Utilization in Weaned Piglets - Cui, Zhijuan; Wang, Xianze; Liao, Simeng; Qi, Ming; Zha, Andong; Zuo, Gang; Liao, Peng; Chen, Yuguang; Guo, Chun; Tan, Bie (Frontiers in Veterinary Science, 2022)
Weaning stress induces the depressed digestive and absorptive capacity and insufficient intestinal energy supply. Medium-chain fatty acid glycerides have shown to improve the growth performance and intestinal barrier function of weaned piglets in the previous study. This study was aimed to investigate the regulation of medium-chain fatty acid glyceride on the nutrient absorption and energy utilization of weaned piglets. Nighty healthy weaned piglets were randomly assigned into five treatments: NP (Normal protein, normal-protein diet no antibiotics included); NC (Negative control, low-protein diet no antibiotics included); PC (Positive control, low-protein diet +75 mg/kg quinocetone, 20 mg/kg virginiamycin and 50 mg/kg aureomycin); MCT (tricaprylin + tricaprin group, low-protein diet + tricaprylin + tricaprin); GML (glycerol monolaurate group, low-protein diet + glycerol monolaurate). The results showed that GML treatment increased the ALP activity, concentrations of serine and methionine, MCT treatment increased concentrations of serine and 3-methyl-histidine but decreased TG concentration in serum. MCT and GML supplementations significantly promoted the lipase activity in the jejunum and ileum, as well as the AMP content in the ileal mucosa. GML addition significantly decreased the contents of butyric acid, isobutyric acid and total volatile fatty acid. In addition, medium chain fatty acid glycerides altered gene expressions involved in lipid metabolism, which showing the increases of AMPK2, CD36 and CGI58 and the decreases of MGAT2 and DGAT2 in the liver, as well as the increases of CD36, CGI58, MGAT2 and DGAT2 in the subcutaneous adipose tissue. These findings showed that medium-chain fatty acid glyceride can effectively improve the absorption of nutrients and lipid metabolism of piglets to meet the energy demand of weaned piglets, and then regulate the growth and development of weaned piglets.